The Invisible Prison: Pathways and Prevention - Brinig, Margaret F (2020)
In this Article, we propose a new strategy for curbing crime and delinquency and demonstrate the inadequacy of current reform efforts. Our analysis relies on our own, original research involving a large, multigenerational sample of unmarried fathers from a Rust Belt region of the United States, as well as the conclusions of earlier researchers. Our own research data are unusual in that they are holistic and multigenerational: the court-based record system we utilized for data collection provided detailed information on child maltreatment, juvenile status and delinquency charges, child support, parenting time, orders of protection, and residential mobility for focal children (the oldest in the family), their siblings, half-siblings, and all parents who grew up in the relevant county. Using other data sources, we were also able to obtain reliable information about adult crime and other high-risk behaviors. Very few crime researchers have had access to data this comprehensive. Our research findings show the incarcerative state in action. Close to one-third (31.7%) of sample fathers had been incarcerated, at least once, as adults, and almost half (49.5%) of those who lived, as teenagers, in the county we investigated had at least one juvenile arrest. Our findings support recent nonpartisan reforms, such as the federal First Step Act, that reduce mandatory sentences and place increased emphasis on substance-abuse treatment. The vast majority of offenders in our sample committed nonviolent offenses and posed no serious public-safety risk. Seventy percent of those with felony convictions also had a known history of substance abuse. However, our data show that current reforms are incapable of significantly reducing criminal misconduct or the disproportionate impact of incarceration on black Americans and the poor. In our sample, adult paternal crime was linked to other high-risk behaviors, significantly correlated with several of the father’s adverse childhood experiences (ACEs), and predicted a number of adverse outcomes in his children. Our data thus contribute to a growing body of research showing that high ACE levels—levels that are typically linked with and reinforced by poverty—significantly increase the risk of criminal behavior as well as physical and mental-health problems, educational and occupational deficits, high-risk behavior, and early death. To successfully reduce the costs of crime, we argue that policymakers must develop a public-health approach. We also argue that, as with virtually all successful public-health campaigns, public policy should focus on prevention programs that reduce risks and shift away from costly and largely ineffective postcrime punishment and rehabilitation strategies